Type 1 diabetes and pro cycling: 10 years of learning from the professionals. (5th April 2022) - Scott, Sam N; Hayes, Charlotte; Castol, Rafael; Fontana, Federico Y
Abstract: People living with type 1 diabetes (T1D) are recommended to undertake regular exercise to maintain health and wellbeing. However, the effects of exercise on glucose concentration are complex, and despite advances in supportive technologies and insulins, exercise remains a challenge for people living with T1D. Despite the challenges, Team Novo Nordisk (TNN) has demonstrated that with planning and determination, people with T1D can successfully pursue endurance sports. TNN has developed, refined, and adapted evidence‐based scientific strategies for managing nutrition and glycaemia in elite‐level athletes with T1D participating in ultra‐endurance events. Advances in technologies, such as continuous glucose monitoring, have facilitated non‐invasive and comprehensive observation of the TNN riders, who are supported by a multidisciplinary team of doctors, coaches, researchers, and nutritionists to formulate individualised data‐driven strategies. This article highlights the current learnings and data‐informed strategies being employed to assist management of diabetes in a professional endurance sport environment, almost 10 years after the publication of 'Lessons from the professionals: diabetes and pro cycling' (2013). In recent years, TNN has placed a high level of emphasis on research to improve safety and athletic performance while also striving to make these insights widely available to benefit the broader community. Copyright © 2022 John Wiley & Sons.